Innovative self-sensing fiber-reinforced cemented sand with hybrid CNT/GNP - Abedi, Mohammadmahdi (2021)
This study is a systematic attempt to develop a self-sensing fiber-reinforced cemented sand (CS) with high physical, mechanical, durability, and piezoresistivity performances. In this route, different concentrations of Dyneema, glass, and polypropylene (PP) fibers were incorporated into CS containing 0.17% hybrid carbon nanotubes and graphene nanoplatelets. The specimens were fabricated using the standard Proctor compaction method and tested at the optimum water content. The mechanical, microstructural, and durability performances of the specimens were evaluated through various types of tests. Further, the piezoresistivity of the specimens was evaluated under compression cyclic loads using the four probes method. The incorporation of 1.0% glass and Dyneema fiber as the optimum percent increased the unconfined compression strength (UCS) (29% and 82%, respectively) and the maximum dry density of the CS; however, reinforcing of the specimens with PP fiber at a concentration in the range of 0.5%-1.5% generally reduced the UCS of the specimens. The pullout test results exhibited a considerable interfacial performance for the Dyneema fiber. The CS reinforced with 1.0% Dyneema and glass fiber demonstrated a lower weight loss after 12 wetting and drying cycles compared to other specimens. The maximum gauge factors were also achieved for Dyneema fiber-reinforced CS. The outcomes of this study, balanced with sustainable issues, contribute to the development of the new era of smart structures, with applications to roller-compacted-concrete dams, rammed earth, and particularly in structural layers in transportation infrastructure.